2016
DOI: 10.15585/mmwr.mm6536e1
|View full text |Cite|
|
Sign up to set email alerts
|

Vital Signs: Disparities in Antihypertensive Medication Nonadherence Among Medicare Part D Beneficiaries — United States, 2014

Abstract: Introduction: Nonadherence to taking prescribed antihypertensive medication (antihypertensive) regimens has been identified as a leading cause of poor blood pressure control among persons with hypertension and an important risk factor for adverse cardiovascular disease outcomes. CDC and the Centers for Medicare and Medicaid Services analyzed geographic, racial-ethnic, and other disparities in nonadherence to antihypertensives among Medicare Part D beneficiaries in 2014. Methods: Antihypertensive nonadherence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…1 Approximately 50% of patients with CVD have suboptimal adherence to their prescribed medications, with deleterious effects on morbidity, mortality, and healthcare costs. 6,7 …”
Section: | Introductionmentioning
confidence: 99%
“…1 Approximately 50% of patients with CVD have suboptimal adherence to their prescribed medications, with deleterious effects on morbidity, mortality, and healthcare costs. 6,7 …”
Section: | Introductionmentioning
confidence: 99%
“…14,18,19 Additionally, a nationallevel study of Medicare beneficiaries found that those who were not prescribed fixed-dose combinations, and who were prescribed more than 1 class of antihypertensives had lower adherence. 5 Strategies characterized as tracking and encouragement were reported to be less frequently used in our study. There may be future growth in this 27 Pharmacists can improve blood pressure control through a variety of mechanisms, including communicating with providers to coordinate medication synchronization, participating in collaborative practice agreements to reduce care fragmentation, and using e-prescribing that has bi-directional messaging with prescribers.…”
Section: Discussionmentioning
confidence: 74%
“…High adherence to antihypertensives has been associated with greater odds of blood pressure control . Yet, cardiovascular‐related medication non‐adherence is common and improving adherence requires multifaceted approaches from various stalkeholders . Thus, efforts to improve antihypertensive adherence is a focus of national efforts to improve blood pressure control and cardiovascular disease outcomes, such as the US Department of Health and Human Services’ Million Hearts © initiative…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Centers for Disease Control and Prevention cited motivational interviewing techniques as opportunities for health care providers to improve antihypertensive medication nonadherence. 9 Beginning health coach training as students would better prepare the next generation of pharmacists to step out of the realm of traditional counseling to improve disease state management and possibly reduce hospital re-admission rates. This year, faculty have expanded the motivational interviewing training and implemented the health coaching strategy with all students in the course.…”
Section: Next Stepsmentioning
confidence: 99%